PS/Silica Aerogel Nanofibers Production for Thermal Insulation - ARAT, REFİK (My University, 2019)
Aerogels are fascinating solid materials made up with over 95% air and less than 5% skeletons [1], With the advantages of an extremely low density of 0.003-0.5 g/cm3, a low thermal conductivity of 0.017-0.021W/m-K and a high specific surface area of 500-1200 m2/g [1-3], aerogels have enormous application potential in various fields, such as thermal insulators, energy conservation, catalyst supports, biomedical engineering and aerospace applications [3- 9]- In this work, silica aerogels were synthesized as stated by Li at al. [10], Commercial polystyrene (PS) was used instead of polymerization of styrene monomers to obtain PS/silica aerogels nanocomposites. Furthermore, nanofiber structure was obtained by electrospinning. The specific surface area, pore volume and particle size of aerogels, which are 590 m2/g, 1.4 cm3/g and 10 nm, respectively, were determined by BET analysis. Thermal gravimetric analysis indicated that the maximum degradation temperature of PS shifted from 412 to 444 °C when silica aerogels content at 10wt%. Regards to improvement in thermal stability, PS/silica aerogels nanocomposites can be a promising candidate for thermal insulation applications.
Keywords: Silica Aerogel; PS/Silica Nanofibers; Electrospinning; Thermal Insulation